Metabolic syndrome after pregnancies complicated by pre‐eclampsia or small‐for‐gestational‐age: a retrospective cohort. (16th October 2014) - Al‐Nasiry, S; Ghossein‐Doha, C; Polman, SEJ; Lemmens, S; Scholten, RR; Heidema, WM; Spaan, JJ; Spaanderman, MEA
Abstract : Objective: To study the prevalence of metabolic syndrome in women after a pregnancy complicated by pre‐eclampsia or small‐for‐gestational‐age (SGA), both epitomes of placental syndrome. Design: A retrospective cohort study. Setting: Single tertiary centre for maternal medicine in the Netherlands. Population: Women with a history of pre‐eclampsia in absence of SGA ( n  = 742) or pregnancy complicated by normotensive SGA ( n  = 147) between 1996 and 2010. Methods: Women were routinely screened for underlying cardiometabolic and cardiovascular risk factors at least 6 months postpartum. Logistic regression analysis was used to calculate the odds ratio and adjusted odds ratio for each group. Adjustments were made for age, maternal height, smoking, parity, and interval between delivery and measurement. Main outcome measures: Prevalence of the metabolic syndrome. Results: The prevalence of the metabolic syndrome in our population was two‐fold higher for women with a history of pre‐eclampsia (13.9%) compared with women with a history of SGA (7.6%). Calculated odds ratios for metabolic syndrome, fasting insulin, HOMA, and microalbuminuria were all higher for women with a history of pre‐eclampsia compared with women with SGA. This difference persisted after adjustment for confounding factors: metabolic syndrome (adjusted odds ratio, aOR 2.11; 95% confidence interval, 95% CI 1.00–4.47) and hyperinsulinaemia (aOR 1.78; 95% CI 1.13–2.81) insulin resistance (HOMAIR ; aOR 1.80; 95% CI 1.14–2.86). Microalbuminuria (aOR 1.58; 95% CI 0.85–2.93) did not reach the level of significance after adjustment for confounding factors. Conclusions: A history of pre‐eclampsia, rather than SGA, was associated with metabolic syndrome, suggesting that it relates to maternal rather than fetal etiology of placental syndrome.